Identification of ancestral knowledge in the Emberá Katío ethnic group on environmental care - Cantero, Elizabeth; Hernández, Elías Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Education in Colombia has difficulties in meeting the needs of indigenous communities and balancing educational programs with the cultural requirements of each community. Indigenous children are forced to adapt to an educational system that is not in accordance with their needs. For this reason, the objective of this work is to identify the ancestral knowledge of the Emberá Katío culture related to caring for the environment and the indigenous relationship with nature. The study methodology is framed in the qualitative approach, with an ethnographic design, the collection of information was carried out by semi-structured interview and observation. As a main conclusion, it is highlighted that the Emberá have a different way of seeing the world, with their own worldview that includes beliefs, practices and traditional customs that define their structure as a people and society, they conceive of the earth as a mother, so they have a relationship of respect for her, which is transmitted to her children through spiritual knowledge and traditional productive practices.